1988
DOI: 10.1016/0035-9203(88)90528-7
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis: in vivo results of therapy with albendazole and praziquantel

Abstract: The effects of albendazole and praziquantel on the growth of Echinococcus multilocularis were studied in cotton rats. Albendazole (20 and 50 mg/kg) reduced parasite weight and increased the length of survival of infected animals but viable infection was present after treatment. In an in vitro system albendazole sulphoxide entered cysts of E. multilocularis passively. Praziquantel 100 mg/kg was ineffective but 500 mg/kg significantly inhibited growth. A combination of albendazole and praziquantel was no more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…We have also reported in vivo activity of albendazole against E multilocularis in an animal model. 9 The present study has produced information concerning the in vivo protoscolicidal action of albendazole and prazquantel after therapy, which concurs with the previous in vitro results in that praziquantel was significantly more effective than The efficacy of albendazolc in reducing the ratc of cyst growth, as measured by parasite weight, was greater than either mebendazole at the same dose or praziluantel at 10 times the dosage. Regression of established disease apparently occurred and animal survival was probably enhanced.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have also reported in vivo activity of albendazole against E multilocularis in an animal model. 9 The present study has produced information concerning the in vivo protoscolicidal action of albendazole and prazquantel after therapy, which concurs with the previous in vitro results in that praziquantel was significantly more effective than The efficacy of albendazolc in reducing the ratc of cyst growth, as measured by parasite weight, was greater than either mebendazole at the same dose or praziluantel at 10 times the dosage. Regression of established disease apparently occurred and animal survival was probably enhanced.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that chemotherapy has little if any effect on the weight of uninfected animals. 9 Ultrastructurally, the germinal layer (Fig. 2) and the tegument of protoscoleces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various degrees of enhanced activity ranging from synergy/addition to partial enhancement were found. Although this is the first in vitro demonstration of enhanced activity of combination therapy using T. solium larval cysts in vitro, enhanced activity has been described in the cestodes T. crassiceps (16) and E. granulosus and E. multilocularis in vitro (12,(25)(26)(27)(28)(29)(30), as well as in imperfect human case series against E. granulosus in vivo (8,33). Kaur et al found enhanced but nonsignificant decrease in estimated time to clearance of single enhancing lesions using combined therapy in NCC compared to single therapy in India T. crassiceps has been used in vitro and in vivo to evaluate effectiveness of cysticidal drugs.…”
Section: Discussionmentioning
confidence: 86%
“…Praziquantel has not been rigorously assessed in the treatment of hydatid disease, but in experimental animals its effect is as good as that of albendazole [21]. Reports suggest that a synergistic effect may occur when albendazole and praziquantel are administered together in humans [8].1The evaluation of patients with hydatid disease who are treated with albendazole is difficult because of the long period needed to assess the outcome in this chronic disease.…”
Section: Discussionmentioning
confidence: 99%